Multipoint Pacing versus conventional ICD in Patients with a Narrow QRS complex (MPP Narrow QRS trial): study protocol for a pilot randomized controlled trial. Issue 1 (December 2016) - Gasparini, Maurizio; Galimberti, Paola; Bragato, Renato; Ghio, Stefano; Raineri, Claudia; Landolina, Maurizio; Chieffo, Enrico; Lunati, Maurizio; Mulargia, Ederina; Proclemer, Alessandro; Facchin, Domenico; Rordorf, Roberto; et al.
Abstract Background Despite an intensive search for predictors of the response to cardiac resynchronization therapy (CRT), the QRS duration remains the simplest and most robust predictor of a positive response. QRS duration of ≥ 130 ms is considered to be a prerequisite for CRT; however, some studies have shown that CRT may also be effective in heart failure (HF) patients with a narrow QRS (<130 ms). Since CRT can now be performed by pacing the left ventricle from multiple vectors via a single quadripolar lead, it is possible that multipoint pacing (MPP) might be effective in HF patients with a narrow QRS. This article reports the design of the MPP Narrow QRS trial, a prospective, randomized, multicenter, controlled feasibility study to investigate the efficacy of MPP using two LV pacing vectors in patients with a narrow QRS complex (100–130 ms). Methods Fifty patients with a standard ICD indication will be enrolled and randomized (1:1) to either an MPP group or a Standard ICD group. All patients will undergo a low-dose dobutamine stress echo test and only those with contractile reserve will be included in the study and randomized. The primary endpoint will be the percentage of patients in each group that have reverse remodeling at 12 months, defined as a reduction in left ventricular end-systolic volume (LVESV) of >15% from the baseline. Discussion This feasibility study will determine whether MPP improves reverse remodeling, as compared with standard ICD, in HF patients who have a narrow QRS complex (100–130 ms). Trial registration ClinicalTrials.gov, NCT02402816 . Registered on 25 March 2015.